2015
DOI: 10.1021/jp510522z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2 Binding on the Nonadiabatic Transition Probability between Singlet and Triplet States of the [NiFe]-Hydrogenase Active Site

Abstract: We investigate the effect of H2 binding on the spin-forbidden nonadiabatic transition probability between the lowest energy singlet and triplet electronic states of [NiFe]-hydrogenase active site model, using a velocity averaged Landau-Zener theory. Density functional and multireference perturbation theories were used to provide parameters for the Landau-Zener calculations. It was found that variation of the torsion angle between the terminal thiolate ligands around the Ni center induces an intersystem crossin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…Yet the consensus is that while both metals may participate, Ni does the bulk of the work, not only because it is optimally positioned near the end of a hydrophobic H 2 transport channel, 324 but also because its unusual geometry is particularly reactive, as indicated by DFT calculations. 310,325 Recent work has suggested that the orientation of Cys ligands has a strong influence on spin densities at Ni and S. 326,327 Furthermore, several computational studies on truncated active sites indicate that rotation of terminal Cys modulates the relative stability of low- and high-spin Ni, 310,328,329 although the protein environment may also have nontrivial effects on Ni electronic structure. 325,330 In the case of a Ni(II)Fe(II) core such as that in Ni-SI a , one would expect square-planar and tetrahedral Ni to give rise to S = 0 and 1 states, respectively.…”
Section: [Nife]-h2asesmentioning
confidence: 99%
“…Yet the consensus is that while both metals may participate, Ni does the bulk of the work, not only because it is optimally positioned near the end of a hydrophobic H 2 transport channel, 324 but also because its unusual geometry is particularly reactive, as indicated by DFT calculations. 310,325 Recent work has suggested that the orientation of Cys ligands has a strong influence on spin densities at Ni and S. 326,327 Furthermore, several computational studies on truncated active sites indicate that rotation of terminal Cys modulates the relative stability of low- and high-spin Ni, 310,328,329 although the protein environment may also have nontrivial effects on Ni electronic structure. 325,330 In the case of a Ni(II)Fe(II) core such as that in Ni-SI a , one would expect square-planar and tetrahedral Ni to give rise to S = 0 and 1 states, respectively.…”
Section: [Nife]-h2asesmentioning
confidence: 99%
“…The mechanisms of these reactions are not completely understood . Our previous studies show that both the lowest energy singlet and triplet states could be important for the reactivity of the [NiFe]‐hydrogenase active site, and therefore, for understanding the catalytic behavior of this system . A model of the active form, Ni‐SI a , of the [NiFe]‐hydrogenase active site was constructed by replacing the cysteine ligands with SCH 3 groups (Fig.…”
Section: Na‐tst Application To the Active Sites Of Metal‐sulfur Proteinsmentioning
confidence: 99%
“…Not surprisingly, the differences between the singlet and triplet states geometries are mostly due to the different values of the torsion angle α between planes p 1 (S1‐Ni‐S2) and p 2 (S3‐Ni‐S4). Thus, this angle can be used as a reasonable approximation to the reaction coordinate connecting the equilibrium geometries of the singlet and triplet states . The singlet and triplet state energies for the geometries interpolated between the equilibrium structures of the two spin states are shown in Figure b.…”
Section: Na‐tst Application To the Active Sites Of Metal‐sulfur Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weighted average with statistical concepts based on the Landau‐Zener (LZ) model was introduced to evaluate the ISC probabilities at the MECP, which is defined as Equation . The LZ probability for the mass‐weighted component of the nuclear velocity perpendicular to the crossing seam and the Maxwell‐Boltzman velocity distribution, as is shown in Equations and . For kinetics of nonadiabatic spin‐forbidden reaction, we roughly estimated the rate constant based on the transition state theory Equation .…”
Section: Computation Methodsmentioning
confidence: 99%